Examining highland youth farmers’ adaptation ability towards climate change impacts - Fadzil, Mohd. Fauzi; Idris, Khairuddin; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2017)
This paper examines the highland youth farmers’ ability to adapt to climate change impacts. This research applied a cross sectional survey involving 184 highland youth farmers from Cameron Highland, Lojing, Moyog and Kundasang. Respondents had a high adaptation level in relation to cognitive (M=3.79). Furthermore, the study concluded a high adaptation level in relation to practice among the respondents (M= 3.89). Interestingly, the respondents used creative initiatives in adapting towards climate change. The study stresses on the need for highland youth farmers to be proactive in strengthening their adaptation ability.